Finansal risklerden korunma aracı olarak tüzel kişilik ve İslam hukuku açısından değerlendirilmesi - Kömürcü, Muhammet Enes (My University, 2025)
Bu çalışma, modern bir kavram olan tüzel kişiliğin İslami finans alanındaki yansımalarını ve risk kavramıyla ilişkisini İslam hukuku açısından incelemeyi amaçlamaktadır. Birinci bölümde tüzel kişiliğin tarihçesi, mahiyeti, ehliyet ve sorumluluk boyutları ele alınarak İslam hukukunda vakıflar ve kamu kurumları üzerinden gelişen hükmî şahsiyet kuramına değinilmiştir. İkinci bölümde, risk kavramı İslâmî ölçütlerle; meşru risk, garar, daman ve ahlâkî risk ayrımları çerçevesinde işlenmiş, tüzel kişiliğin “perde kaldırma” uygulamaları ve ortaya çıkabilecek şer‘î riskler tartışılmıştır. Üçüncü bölümde ise Varlık Kiralama Şirketleri ve Katılım Kefalet Şirketleri modelleri vaka analizleriyle incelenmiş; bu yapılar üzerinden risk yönetimi, sınırlı sorumluluk ve şer‘î uyum açısından incelenmiştir. Tüzel kişiliğin sahip olduğu sınırlı sorumluluk ve zimmet kavramları ayrıntılı olarak analiz edilmiş, tüzel kişilikle ilgili ahlaki ve etik değerler üzerine tartışmalar yapılmıştır. Çalışma sonucunda, İslam hukukunun, modern ticaretin dinamik ihtiyaçlarına uygun bir biçimde tüzel kişilik kavramını benimseyip uygulayabileceği ancak bu uygulamanın klasik fıkhın temel prensiplerine ve ahlaki değerlere sıkı bir şekilde bağlı olması gerektiği vurgulanmıştır. Çalışma, klasik fıkhî ilkeler ile çağdaş finansal yapılar arasında bir köprü kurarak, İslam hukukunun bu kavramlara nasıl yaklaşabileceğine dair bütüncül bir değerlendirme sunmaktadır. Tüzel kişiliğin tanımlanması, pratikteki varlığı ve kendi içinde yer aldığı teorik yapı bazı açılardan mükemmel bir uyuma sahip değildir. Bu durum İslam hukuku açısından tüzel kişiliğin uygunluğunu tespit etmeyi güçleştirmektedir. Günümüzde ortaklığa dair kavramların tüzel kişilik ile olan ilişkisi, bu yapının pratik işlevselliğini göz önünde bulundurarak incelenmektedir. Tezimizde bu pratik gerçekliğin dışında teorik temelleri açısından da tüzel kişiliğin konumunu tespit etmeye gayret edilmiştir. Tüm bu değerlendirmelerin bir arada yapılmasıyla tüzel kişiliğin İslam hukuku açısından değeri ve yerini tespit etmek mümkün olabilmektedir.

This study aims to examine the reflections of the modern concept of legal personality in the field of Islamic finance and its relationship with the concept of risk from an Islamic law perspective. In the first chapter, the history, nature, legal capacity, and liability dimensions of legal personality are addressed, and the theory of legal personality that developed in Islamic law through waqfs, and public institutions is discussed. In the second chapter, the concept of risk is analyzed according to Islamic criteria, delineating distinctions between legitimate risk, gharar, daman, and moral risk. Additionally, the potential Shariah risks that may arise from “piercing the corporate veil” of legal personality are debated. In the third chapter, models of Asset Leasing Companies and Participation Finance Surety Company are examined through case studies. Using these structures as a basis, aspects of risk management, limited liability, and Shariah compliance are analyzed. In this context, the principle of limited liability and the concept of zimmet inherent to legal personality are scrutinized in detail, and discussions are presented on the ethical and moral values related to legal personality. As a result of the study, it is emphasized that Islamic law can adopt and implement the concept of legal personality in a manner suited to the dynamic needs of modern commerce, but this implementation must remain strictly bound to the fundamental principles of classical fiqh and to moral values. The study builds a bridge between classical fiqh principles and contemporary financial structures, offering a holistic evaluation of how Islamic law can approach these concepts. However, the definition of legal personality, its practical existence, and the theoretical framework to which it belongs are not perfectly aligned in certain respects, which makes it difficult to determine the suitability of legal personality from an Islamic law perspective. Today, the relationship between partnership-related concepts and legal personality is examined with a view to the practical functionality of this construct. In this thesis, an effort has also been made to ascertain the position of legal personality from the standpoint of its theoretical foundations, beyond this practical reality. By considering all of these factors together, it becomes possible to determine the value and place of legal personality from the perspective of Islamic law.
Legal personality as a tool of protection from financial risks and its evaluation in terms of Islamic law
Keywords: ahlaki risk Islamic finance; company; Islamic law; İslam hukuku; İslami finans; Juristic person; legal personality; moral risk; risk; shariah risk; şer’i risk; şirket; Tüzel kişiler; tüzel kişilik